Сага о шпионской любви: [роман] / И. Атаманенко - Атаманенко Игорь Григорьевич (Остросюжет, 2011)
Экземпляры: (20170710) / Инвентарный номер: 35963 / Цена: 183.38 / Сис.шифр: Р2 / Авт.знак: А 92 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6